2014
DOI: 10.1371/journal.pone.0103133
|View full text |Cite
|
Sign up to set email alerts
|

Targeted High-Throughput Sequencing Identifies Pathogenic Mutations in KCNQ4 in Two Large Chinese Families with Autosomal Dominant Hearing Loss

Abstract: Autosomal dominant non-syndromic hearing loss (ADNSHL) is highly heterogeneous, among them, KCNQ4 is one of the most frequent disease-causing genes. More than twenty KCNQ4 mutations have been reported, but none of them were detected in Chinese mainland families. In this study, we identified a novel KCNQ4 mutation in a five generation Chinese family with 84 members and a known KCNQ4 mutation in a six generation Chinese family with 66 members. Mutation screening of 30 genes for ADNSHL was performed in the proban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…One microgram of gDNA from peripheral blood samples was fragmented to 200–300 base pairs using an ultrasonoscope (Covaris S2, Massachusetts, USA). End‐repair, adenylation and adapter ligation were performed for library preparation following Illumina's protocol (Wang et al., ). The same amount of the library was pooled and then hybridized to the customized capture array (NimbleGen, Roche), which had exons, splicing sites and immediate flanking intron sequences of 127 genes (Appendix ), including most of the known genes involved in nonsyndromic hearing loss and those involved in some relatively common syndromic hearing loss conditions.…”
Section: Methodsmentioning
confidence: 99%
“…One microgram of gDNA from peripheral blood samples was fragmented to 200–300 base pairs using an ultrasonoscope (Covaris S2, Massachusetts, USA). End‐repair, adenylation and adapter ligation were performed for library preparation following Illumina's protocol (Wang et al., ). The same amount of the library was pooled and then hybridized to the customized capture array (NimbleGen, Roche), which had exons, splicing sites and immediate flanking intron sequences of 127 genes (Appendix ), including most of the known genes involved in nonsyndromic hearing loss and those involved in some relatively common syndromic hearing loss conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The KCNQ4 protein consists of six transmembrane domains, a pore region, and two intracellular termini (Dominguez & Dodson, ). The majority of mutations in KCNQ4 linked to hearing loss are clustered around the pore region (Wang et al., ) and lead to loss of KCNQ4‐mediated potassium currents. KCNQ4 is assembled in homo‐ or heterotetramer pore‐forming subunits; therefore, defects in a single subunit can impair channel function of the tetramer, explaining the development of hearing loss in individuals heterozygous for KCNQ4 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The novel missense mutation p.G296D is in the pore region of KCNQ4, where also resides the mutations p.L274H [23], p.W275R [24], p.W276S [12, 15, 21, 22], p.L281S [20], p.G285S [4, 24], p.G285C [4], p.G287R [13], p.P291S [18], p.P291L [18] and p.G296S [7]. In a previous study, Mencia et al reported that the mutation c.886G > A (p.G296S) in KCNQ4 is pathogenic [7].…”
Section: Discussionmentioning
confidence: 99%
“…The age of onset of hearing loss caused by p.Q71fs in the N-terminal, p.G285C in the pore region, and p.A349Pfs in S6trans is in the first decade of life [15, 23, 25]. However, the average age of onset of hearing loss associated with the mutations p.W275R, p.G285S and p.G296S, located in the pore region, ranges from the first to the fourth decade [4, 7, 24]. In our study, the age of onset of hearing loss in the affected family members was in the second to third decades of life.…”
Section: Discussionmentioning
confidence: 99%